CARNIAN REEF BIOTA FROM A MEGABRECCIA OF THE HAWASINA COMPLEX (AL AQIL, OMAN) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1999)
Carnian reef biota and brachiopods of the Misfah Formation (Hawasina complex) from a locality near the town of Al Aqil in Oman are described. A new brachiopod species, Oxycolpella arabica n. sp. is described. The composition of the Carnian reef biota in Oman is similar to those known from the Alpine-Mediterranean region. However, differences exist in the microfauna of reef dwellers, e.g. foraminifers. New stratigraphic data based on reef organisms and conodonts are presented.